1977
DOI: 10.1002/j.1537-2197.1977.tb15734.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Ultrastructural Aspects of Metaphloem Sieve Elements in the Aerial Stem of the Holoparasitic Angiosperm Epifagus Virginiana (Orobanchaceae)

Abstract: A light and electron microscope investigation was conducted on phloem in the aerial stem of Epifagus virginiana (L.) Bart. Tissue was processed at field collection sites in an effort to overcome problems resulting from manipulation. At variance with earlier accounts, Epifagus phloem consists of sieve elements, companion cells, phloem parenchyma cells, and primary phloem fibers. The sieve elements possess simple sieve plates and the phloem is arranged in a collateral type of vascular bundle. In addition, this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In two other genera of Orobanchaceae, Orobanche and Epifagus, sieve elements have been conclusively demonstrated (DOERR & KOLLMANN 1975;WALSH & POPOVICH 1977), and phloem may therefore be expected in at least the stem also of Boschniakia. In the tissues adjoining the interface, however, we have failed to find any phloem-like cells.…”
Section: Resultsmentioning
confidence: 93%
“…In two other genera of Orobanchaceae, Orobanche and Epifagus, sieve elements have been conclusively demonstrated (DOERR & KOLLMANN 1975;WALSH & POPOVICH 1977), and phloem may therefore be expected in at least the stem also of Boschniakia. In the tissues adjoining the interface, however, we have failed to find any phloem-like cells.…”
Section: Resultsmentioning
confidence: 93%
“…Howeuer, no "sieue tubes" with sieue plates were obserued by Perciual ( 1931), leading him to the conclude that they had been eliminated in this aduanced parasite. Perciual's ( 1931) obseruation stands in conflict with Boeshore ( 1920), who concluded that from the hemiparasitic figworts through the holoparasitic broomrapes Of interest, the ultrastructural study of Walsh and Popouich { 1977) found that the sieue tube members in the aerial stem of the broomrape Epifagus uirginiana lacked P-protein, a condition nouel to a holoparasite. Further study, particularly at the ultrastructural leuel, is needed to confirm the presence and significance of P-protein in the sieue elements of holoparasitic angiosperms.…”
Section: Secondary Growthmentioning
confidence: 95%
“…Further, Boeshore ( 1920) concluded that a perennial parasite fauored selection for host-specificity. The aduanced holoparasitic broomrapes are eHemplified by the monotypic genus Epif agus which parasitizes only members of the genus Fagus (Cooke and Schiuely 1904;Walsh and Popouich 1977), C:onopholis which parasitizes members of the genus Ouercus (Boeshore 1920, Perciual 1931, and Boschniakia hookeri which parasitizes only perennial genera of the Ericaceae. This study confirms that B.…”
Section: Secondary Growthmentioning
confidence: 99%
See 2 more Smart Citations